Stereo Operative Atlas of Micro Ear Surgery - Dai, Pu; Han, Dong-yi; Cousins, Vincent C.; Song, Yue-shuai (Springer Singapore : Imprint: Springer, 2017)
This book introduces readers to modern micro ear surgery procedures employing 3-D methods. Divided into 5 chapters, it explores 43 micro ear surgery operations, while 418 pairs of stereoscopic images illustrate each procedure in 3-D detail. Using the operating microscope, which provides true stereo vision through its two-eye lens system, the authors present various micro ear surgeries, including mastoid and middle ear surgery, facial nerve surgery, inner ear surgery, and lateral skull base surgery. For each pair of stereoscopic images, readers can find the anatomic structures captured from two different angles, and will learn how to use stereoscopic 3-D methods to view the anatomic structures hidden deep in the temporal bone. As such, the book offers a valuable guide book and reference work for doctors specializing in otology, neurology and related fields.
Keywords: Medicine.; Otorhinolaryngology.; elektronické knihy; electronic books